High intrinsic oxidative stress may underlie selective vulnerability of the hippocampal CA1 region - Wang, Xinkun; Pal, Ranu; Chen, Xue-wen; Limpeanchob, Nanteetip; Kumar, Keshava N.; Michaelis, Elias K. (Brain research. Molecular brain research., 2005)
Oxidative stress (OS) causes extensive cell death in the CA1 but not the CA3 region of the hippocampus. We found that the CA1 region of hippocampus explants, cultured under normal conditions, had significantly higher superoxide levels and expressed both anti-oxidant genes and genes related to the generation of reactive oxygen species at significantly higher levels than the CA3. These observations were indicative of high intrinsic OS in CA1.